Effects of Hydroxytyrosol against Lipopolysaccharide-Induced Inflammation and Oxidative Stress in Bovine Mammary Epithelial Cells: A Natural Therapeutic Tool for Bovine Mastitis - Roberta Fusco; Marika Cordaro; Rosalba Siracusa; Alessio Filippo Peritore; Ramona D'Amico; Patrizia Licata; Rosalia Crupi; Enrico Gugliandolo (MDPI AG, 2020)
Background: Bovine mastitis is a growing health problem, affecting both welfare of dairy cattle and milk production. It often leads to chronic infections, disturbing the quality of milk and resulting in cow death. Thus, it has a great economic impact for breeders. Methods: In this study, we evaluated the protective effect of hydroxytyrosol-a natural molecule which is the major constituent of many phyto-complexes-in an in vitro model of mastitis induced by LPS (1μg/mL). Results: Our results showed that hydroxytyrosol (10 and 25 μM) was able to prevent the oxidative stress induced by LPS (intracellular ROS, GSH and NOX-1) and the consequently inflammatory response (TNF-α, IL-1β and IL-6). The protective effect of hydroxytyrosol is also related to the enhancement of endogenous antioxidant systems (Nrf2, HO-1, NQO-1 and Txnrd1). Moreover, hydroxytyrosol showed an important protective effect on cell functionality (α-casein S1, α-casein S2 and β-casein). Conclusions: Taken together, our results showed a significant protective effect of hydroxytyrosol on oxidative stress and inflammatory response in MAC-T cells. Thus, we indicated a possible important therapeutic role for hydroxytyrosol in the prevention or management of bovine mastitis.